2020
DOI: 10.2147/oaem.s245221
|View full text |Cite
|
Sign up to set email alerts
|

<p>Knowledge and Acceptability of Human Papillomavirus Vaccination and Text Message Reminders for Adolescents in Urban Emergency Departments: A Pilot Study</p>

Abstract: Purpose: Cervical, oropharyngeal and anogenital cancers are vaccine-preventable diseases, but human papillomavirus (HPV) vaccination coverage in the US remains poor overall with regional variations in vaccination rates. We explore the acceptability by adolescents and their parents of HPV vaccination and text message reminders in the non-traditional setting of the emergency department (ED). Patients and Methods: The modified validated Carolina HPV Attitudes and Beliefs Scale (CHIAS) survey was administered at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
(24 reference statements)
1
2
0
2
Order By: Relevance
“…We found significant gaps in knowledge about the HPV vaccine’s indication and effects, especially for males and for HNC prevention. These findings are similar to prior studies on knowledge gaps about HPV and HPV prevention among both adults and adolescents, although information related to adolescents and especially children is limited [24] , [25] , [26] .…”
Section: Discussionsupporting
confidence: 90%
“…We found significant gaps in knowledge about the HPV vaccine’s indication and effects, especially for males and for HNC prevention. These findings are similar to prior studies on knowledge gaps about HPV and HPV prevention among both adults and adolescents, although information related to adolescents and especially children is limited [24] , [25] , [26] .…”
Section: Discussionsupporting
confidence: 90%
“…Prior studies have shown that increased knowledge of HPV was correlated with vaccination status 12,23,24 . Similarly, our study found that cumulative HPV score was highly correlated with vaccination status.…”
Section: Discussionmentioning
confidence: 98%
“…Prior studies have shown that increased knowledge of HPV was correlated with vaccination status [ 13 , 24 , 25 ]. Similarly, our study found that cumulative HPV score was highly correlated with vaccination status.…”
Section: Discussionmentioning
confidence: 99%